Dissemination: Education Teacher Based on Gatra Eka Dharma Catur - Marzuki Marzuki; Sri Utami; Suhardi Marli (Universitas Tanjungpura, 2018)
The problem of learning in primary schools is still prevalent in Melawi Regency is the image of teaching teachers who are still not integrated and cultivate the values contained in Catur Gatra (Pancasila, Teacher Hymn, Teacher Competence and Professionalism). Basically, this gatra catur is a unity of noble devotion. To practice and practice it requires a change of mindset - the teacher changes the paradigm of traditional teaching patterns to the mindset and act of educating contemporaries called change